Genome-Wide Analysis of the Phospholipase D Family in Five Cotton Species, and Potential Role of GhPLD2 in Fiber Development and Anther Dehiscence - Ma, Changkai; Zhang, Qian; Lv, Jiaoyan; Qiao, Kaikai; Fan, Shuli; Ma, Qifeng; Zhang, Chaojun (Frontiers in Plant Science, 2021)
Phospholipase D (PLD) and its hydrolysis product phosphatidic acid, play an important role in the regulation of several cellular processes, including root growth, pollen tube elongation, and microtubule reorganization. Here, we systematically identified and analyzed the membership, characterization, and evolutionary relationship of PLDs in five species of cotton. The results of the transcriptomic analysis suggested that the evaluated PLD genes showed high expression levels in anther tissue and during the fiber initiation and elongation periods. Quantitative real-time polymerase chain reaction showed differential expression of GhPLD genes in the anthers of photoperiod sensitive male sterility mutant 5 (psm5). Previous research on multiple stable quantitative trait loci also suggests the role of PLD genes in the fiber development. Further analyses showed that GhPLD2 protein is localizes to the plasma membrane. The virus-induced gene silencing of GhPLD2 in cotton seedlings repressed its expression by 40%–70%, which led to a reduction in ROS levels, 22% anther indehiscence, and disrupted fiber initiation and elongation. Thus, we inferred that GhPLD2 may promote ROS production, which, in turn, may regulate anther dehiscence and fiber development.